Determination Of The Effects Of pH and Adsorption Isotherm Of Pb(II) Metal Ions by Using Activated Carbon From Spent Coffee Grounds - petrick effendi; irfan saputro; tutun nugraha (Liaison Journal of Engineering, 2022)
Caffein, tannin, and polyphenol contents in a substance is an important parameter to determine the hazardous level of the substance. This makes the spent coffee ground considered as a hazardous waste. Lead, on the other hand, is considered as toxic heavy metal because of its ability to pollute water ecosystem. In this study, the spent coffee ground was activated by activated carbon then it was used to adsorb lead ion [Pb(II)]. The effect of pH and the adsorption type of the activated carbon used to adsorb lead ion were studied. Several steps such as brewing, drying, and carbonizing under a specific condition were used to obtain the samples of spent coffee ground. The samples were then activated chemically by using HCl and then washed by using deionized water, and dried. The result shows that the moisture content of the activated carbon from the spent coffee ground was 11.32 ± 0.03%, and its pores size formed was 8.50 ± 4.11 nm. The maximum amount of adsorption was occurred at pH 3 and it followed the Langmuir type of adsorption isotherm. The maximum adsorption capacity was 4.97 ± 0.16 mg/gr for each gram of adsorbent which was the activated carbon from the spent coffee ground.Keywords: Spent Coffee Ground; Activated Carbon; pH; SEM; Adsorption Isotherm